The temporal and spatial expression of sclerostin and Wnt signaling factors during the maturation of posterolateral lumbar spine fusions. Issue 1 (25th June 2020) - Rodriguez‐Feo, John; Fernandes, Lorenzo; Patel, Anuj; Doan, Thanh; Boden, Scott D.; Drissi, Hicham; Presciutti, Steven M.
Abstract: The bone healing environment in the posterolateral spine following arthrodesis surgery is one of the most challenging in all of orthopedics and our understanding of the molecular signaling pathways mediating osteogenesis during spinal fusion is limited. In this study, the spatial and temporal expression pattern of Wnt signaling factors and inhibitors during spinal fusion was assessed for the first time. Bilateral posterolateral spine arthrodesis with autologous iliac crest bone graft was performed on 21 New Zealand White rabbits. At 1‐, 2‐, 3‐, 4‐, and 6‐weeks, the expression of sclerostin and a variety of canonical and noncanonical Wnts signaling factors was measured by qRT‐PCR from tissue separately collected from the transverse processes, the Outer and Inner Zones of the fusion mass, and the adjancent paraspinal muscle. Immunohistochemistry for sclerostin protein was also performed. Sclerostin and many Wnt factors, especially Wnt3a and Wnt5a, were found to have distinct spatial and temporal expression patterns. For example, harvesting ICBG caused a significant increase in sclerostin expression. Furthermore, the paraspinal muscle immediately adjacent to the transplanted ICBG also had significant increases in sclerostin expression at 3 weeks, suggesting new potential mechanisms for pseudarthroses following spinal arthrodesis. The presented work is the first description of the spatial and temporal expression of sclerostin and Wnt signaling factors in the developing spine fusion, filling an important knowledge gap in the basic biology of spinal fusion and potentially aiding in the development of novel biologics to increase spinal fusion rates. Abstract : In this study, the temporal and spatial expression of sclerostin and Wnt signaling factors during a developing posterolateral spine fusion was determined for the first time. Most of the canonical and noncanonical Wnt factors and inhibitors that were assessed were found to have distinct spatial and temporal expression patterns and those patterns were found to differ between successful fusions and nonunions, suggesting new molecular mechanisms for the development of pseudarthroses following spinal arthrodesis. This fills an important knowledge gap in the basic biology of spinal fusion and may aid in the development of novel biologics to increase spinal fusion rates.